2000
DOI: 10.1262/jrd.46.245
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Serum Levels of Inhibin, FSH, LH and Testosterone in Holstein Bulls.

Abstract: Abstract.It has been well demonstrated that the quantity and quality of the semen obtained from bulls improve with age. To understand the relationship between the semen characteristics and hormonal conditions in Holstein bulls, age-related changes in serum levels of inhibin, FSH, LH and testosterone were investigated. One hundred three Holstein bulls were divided into 11 age-groups as 2.5 (n=10), 6.5 (n=10), 12 (n=12), 24 (n=9), 36 (n=10), 48 (n=12), 60 (n=13), 72 (n=8), 84 (n=5), 96 (n=8) and 108 (n=6) months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…This is probably the cause of the decrease in circulating inhibin levels in bulls after 20 weeks of age, in spite of the increase in the testicular contents of inhibin. We found no correlation between the FSH profile and the inhibin A or total inhibin profile; this finding is not consistent with previous reports of a negative [8,9] or positive correlation [10]. The discrepancy between these previous studies and ours is not readily explained, but our determination of the inhibin and FSH profiles was more precise because we used more frequent blood sampling (1-week intervals) than was used in these other studies (2-to 12-week intervals).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is probably the cause of the decrease in circulating inhibin levels in bulls after 20 weeks of age, in spite of the increase in the testicular contents of inhibin. We found no correlation between the FSH profile and the inhibin A or total inhibin profile; this finding is not consistent with previous reports of a negative [8,9] or positive correlation [10]. The discrepancy between these previous studies and ours is not readily explained, but our determination of the inhibin and FSH profiles was more precise because we used more frequent blood sampling (1-week intervals) than was used in these other studies (2-to 12-week intervals).…”
Section: Discussioncontrasting
confidence: 99%
“…The circulating levels of total inhibin and inhibin A reached a plateau by 14 weeks of age and then decreased as the bulls aged, and the changes in total inhibin were similar to previous findings [9,10]. We can expect that a combination of testicular inhibin content and the testis weight to body weight ratio contributes to changes in the circulating concentrations of inhibin.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This type of relationship between inhibin and testosterone is also seen in land mammals and it has been reported that the circulating inhibin levels in male cattle were high prior to sexual maturity compared with levels after sexual maturity [8,13]. Although the exact mechanism of inhibin decrease and testosterone increase after sexual maturity is not known, it could be due to suppression of gonadotropin-releasing hormone secretion in the hypothalamus by the high testosterone concentration.…”
Section: Discussionmentioning
confidence: 75%
“…A suite of molecular pathways is regulated by an interdependent complement of hormones including testosterone, FSH, inhibin and activin, which rise and fall in a specified sequence during prepuberty and peri-puberty to result in functional spermatozoa in the adult bull (Evans et al 1996;Matsuzaki et al 2000;Kaneko et al 2001). This sequence is known to be disrupted by nutritional intervention during the preweaning period (Brito et al 2007b(Brito et al , 2007c possibly mediated by metabolic hormones (i.e.…”
Section: Introductionmentioning
confidence: 99%